Application of livelihood vulnerability index in evaluating household’s livelihood vulnerability to climate change in Can Gio district, Ho Chi Minh city, Vietnam - Nguyen Phuong Tan Le; Nguyen Khoi Dao (Vietnam Journal of Science, Technology and Engineering, 2021)
Climate change is a global problem; however, its effects vary from region to region, country to country, district to district, and community to community. Climate change has profoundly impacted the livelihoods of households reliant on climatic condi- tions in Vietnam’s coastal regions, both directly and indirectly. This research employs the livelihood vulnerability index (LVI) to gauge household vulnerability to climate change effects in one of Vietnam’s most vulnerable regions - the Can Gio coastal district of Ho Chi Minh city. Through a survey encompassing 107 households across six communes and one town within Can Gio, LVI assessments were conducted at both district and commune levels. Findings indicate a moderate vulnerability level for Can Gio district (LVI=0.303), with Ly Nhon commune (LVI=0.334) emerging as the most vulnerable among the surveyed areas. Furthermore, livelihood strategies (0.516), socio-demographic profiles (0.391), and food security (0.385) significantly contribute to determining livelihood vulnerability across the seven surveyed communes. This study underscores the urgency of addressing climate change impacts on coastal livelihoods and highlights the nuanced vulnerabilities within specific communities, providing insights crucial for targeted adaptation and resilience-building efforts in vulnerable regions.